Precarious Meritocracy: Contractual Status, Performance Anxiety, and the Paradox of Efficient Leadership in Public Schools - Javed Ali Rajpar; Abul Ala Mukhtar; Shahid Hussain Wassan (Journal of Religion and Society, 2026)
The systemic failure of the education process to improve student outcomes has been historically described as a result of patronage, seniority-driven promotions and the lack of professional responsibility in the recruitment of school head teachers (Valero et al., 2018). The Government of Sindh in turn responded by instituting a neoliberal reform based on the recruitment on merit provided by third party testing services namely Sukkur IBA University Testing Services (STS). Although these "IBA head teachers" have been able to perform miraculously to enhance the infrastructure of their schools, teacher punctuality as well as community participation, the achievements are inseparably connected with their precarious contractual position. This qualitative multiple case study of schools in District Khairpur argues, based upon the notion that its high performance is not a simple product of individual merit but is essentially constituted by its job insecurity, a phenomenon that is theorized here as the so-called precarious drive. The study examines the ways in which the state captures change capital through the performance anxiety of such leaders through the prism of performative governmentality and neoliberal subjectivity. Although Taluka Education officers (TEOs) are reported to be very satisfied with these visible improvements in schools, the lack of regularization in the head teachers leads them to deep feelings of stress in the future. This report finds that the existing reform model presents a performance-precarity paradox: the reform model effectively evades patronage in the short term, but it is an unsustainable and unethical model of incentives that swaps individual burnout with short-lived systemic temporary benefits. This paper provides analytical reflections on global education policy, outlining the harm of precarity as one of the principal instruments of governmental transformation. Keywords: Contractual Head Teachers, Performance-Precarity Paradox, Precarious Drive, Neoliberal Education Reform, Performative Governmentality, Neoliberal Subjectivity, New Public Management (NPM), Audit culture, Merit-based recruitment